2023
DOI: 10.58803/saa.v2i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Zoonotic Significance of Toxocariasis in Humans: The Role of Toxocara canis

Ali Jahanmahin,
Hassan Borji

Abstract: Toxocariasis is a zoonotic disease caused by the parasite Toxocara canis, with significant effects on human health. This article provided a comprehensive overview of the importance of complications of Toxocara canis infection. The introduction highlighted the relevance of zoonotic diseases and introduced toxocariasis as a specific example. The subsequent sections delved into toxocariasis, covering its transmission, lifecycle, host specificity, and primary sources of human infection. The epidemiology section pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…Причиною цих захворювань можуть бути паразити, бактерії, віруси та грибки, вплив котрих може коливатися від незначного до тяжкого та навіть смертельного. Розуміння епізоотології, етіології, патогенезу та лікування зоонозних захворювань має вирішальне значення для захисту як людей, так і тварин (Jahanmahin & Borji, 2023).…”
Section: вступunclassified
“…Причиною цих захворювань можуть бути паразити, бактерії, віруси та грибки, вплив котрих може коливатися від незначного до тяжкого та навіть смертельного. Розуміння епізоотології, етіології, патогенезу та лікування зоонозних захворювань має вирішальне значення для захисту як людей, так і тварин (Jahanmahin & Borji, 2023).…”
Section: вступunclassified
“…Toxocara canis is an intestinal parasite found mainly in dogs (Macpherson, 2013). However, it can also infect humans, leading to the development of a disease known as human toxocariasis (Jahanmahin and Borji, 2023). This occurs when someone accidentally ingests the parasite's eggs through contact with contaminated soil or objects.…”
Section: Toxocara Canismentioning
confidence: 99%
“…This occurs when someone accidentally ingests the parasite's eggs through contact with contaminated soil or objects. T. canis has been investigated for its potential anticancer effects (Oikonomopoulou et al, 2013;Jahanmahin and Borji, 2023;). Despite T. canis infections most commonly affecting the liver, lungs, and eyes in humans, Garn et al (2021) indicated that exposure to T. canis antigens may reduce the risk of certain types of cancer, such as breast and colon cancers (Garn et al, 2021).…”
Section: Toxocara Canismentioning
confidence: 99%